MR Diffusion Tensor Imaging, Fiber Tracking, and Single-Voxel Spectroscopy Findings in an Unusual MELAS Case - Ducreux, Denis (AJNR Am J Neuroradiol, 2005)
Summary: A 23-year-old man was admitted to the intensive care unit for respiratory failure, global lower and upper limb palsy, and higher cognitive function deterioration. Imaging, performed with a combination of the MR diffusion tensor imaging, fiber tracking, and MR spectroscopy, suggested the diagnosis of an acute severe unusual mitochondrial encephalopathy, lactic acidosis, and strokelike event, which was confirmed by muscle biopsy, but fiber tracking showed unexpected unaltered white matter tracts.